Analisis Geometri Peledakan Guna Mendapatkan Fragmentasi Batuan yang Diinginkan untuk Mencapai Target Produktivitas Alat Gali Muat Pada Kegiatan Pembongkaran Lapisan Tanah Penutup (Overburden) di Pit Menara Utara, PT. Arkananta Apta Pratista Job Site PT.KPUC, Malinau, Kalimantan Utara - Sahrul Ramadana; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. Overburden digging process at North Tower Pit was carried out by blasting. The results of the observation from the actual blasting geometry carried out by the company in blasting activities, it produces blasting fragmentation which boulder size is ±25%, the effect is diggability of the digging tool is not maximum and productivity target of the tool at 800bcm/hour can not be achieved. This study aims to optimize blasting geometry to minimize the number of boulder so that the loading activities become more effective and productivity target can be achieved. The research method is carried out by giving blasting geometry recomendation based on R.L.Ash and ICI Explossives theories and it is done on the both applications which is carried out in the field so that it get the optimum blast plan. Based on the results of the both applications of blasting geometric plans, it is recommended that the geometry plan of blasting is burden: 5.3m, space: 8.5m, stemming: 4,6m, subdrilling: 1m, bench height: 8m, the depth of explosive hole: 9m, powder colomn: 4.4m, and powder factor: 0.33kg/bcm where the boulder of size fragmentation which is produced 10.82%, digging time is 10.76 seconds, bucket fill factor is 64.56%, and the productivity of the digging tool is 865.44bcm/hour.Keywords: Blasting Geometry, Blasting Fragmentation, Digging Time, Bucket Fill Factor, Productivity of Digging Tool